2016
DOI: 10.1136/tobaccocontrol-2015-052734
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Electronic Nicotine Delivery System use and smoking abstinence at 6 months: a descriptive study of callers to employer and health plan-sponsored quitlines

Abstract: ENDS users not using ENDS to quit smoking were less successful at quitting at 6-month follow-up compared with callers using ENDS to quit smoking and callers who did not use ENDS at programme registration. Incorporating reasons for ENDS use may be important for future studies examining the role of ENDS in tobacco cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
1
24
1
Order By: Relevance
“…666 Some prospective studies with loosely defined comparison groups report that vaping may be associated with no change or negative correlations with cessation. 323,393,522,667670 This stands in contrast to other studies with more-precise measures of how ENDS were used (e.g. duration of use, type of device, use specifically for cessation), which suggest that regular, more intensive vaping can facilitate quit attempts and cessation.…”
Section: Evidence Synthesiscontrasting
confidence: 73%
See 1 more Smart Citation
“…666 Some prospective studies with loosely defined comparison groups report that vaping may be associated with no change or negative correlations with cessation. 323,393,522,667670 This stands in contrast to other studies with more-precise measures of how ENDS were used (e.g. duration of use, type of device, use specifically for cessation), which suggest that regular, more intensive vaping can facilitate quit attempts and cessation.…”
Section: Evidence Synthesiscontrasting
confidence: 73%
“…The conclusions from the longitudinal 323,393,522,555,575,577,667,669,670,679,680 and cross-sectional studies 350,395,463,532,555,575,679,681 reporting negative correlations between those who tried ENDS and smoking cessation have serious limitations, including: selection bias (e.g., smokers who quit by using ENDS were excluded from the sample), inadequate measures of exposure (e.g., ever use in one’s lifetime) to test for a cessation indication, and confounders (e.g., smokers who have repeatedly failed to quit are more likely to try ENDS). 668,682,683 This is similar to studies of NRT and smoking cessation in which some observational studies showed negative correlations, 684,685 whereas >80 RCTs of NRT show strong positive cessation effects.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Furthermore, several reasons for initiating e-cigarettes may have increased the risk of continued use of e-cigarettes [19]. A study has reported that the reasons for e-cigarette use were related to future smoking cessation among adults [20]. Smokers who used e-cigarettes for smoking cessation showed a higher smoking cessation rate, whereas those with other reasons showed lower smoking cessation rates than non-e-cigarette users [20].…”
Section: Introductionmentioning
confidence: 99%
“…A study has reported that the reasons for e-cigarette use were related to future smoking cessation among adults [20]. Smokers who used e-cigarettes for smoking cessation showed a higher smoking cessation rate, whereas those with other reasons showed lower smoking cessation rates than non-e-cigarette users [20]. Some studies have reported predictors of continued e-cigarette use [19] and the reasons for experimentation among adolescents [21]; however, few have investigated the reasons for initiation regarding the intensity of e-cigarette use.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies examining changes in smoking and vaping have generally relied on self-reported smoking and vaping (e.g., Adkison et al, 2013;Etter & Bullen, 2014;Prochaska & Grana, 2014;Vickerman, Carpenter, Altman, Nash, & Zbikowski, 2013;Vickerman et al, 2016). Even when an objective measure of smoking (e.g., breath CO) was obtained, it was generally at fixed, weekly time points or during follow-up visits (e.g., Adriaens et al, 2014;Caponnetto et al, 2013;Caponnetto, Polosa, Russo, Leotta, & Campagna, 2011;Halpern et al, 2018;Jorenby, Smith, Fiore, & Baker, 2017;Manzoli et al, 2015;Tseng et al, 2016;Wagener et al, 2014).…”
mentioning
confidence: 99%